Productivity, Profitability and Resource Use Efficiency: A Comparative Analysis between Conventional and High Yielding Rice in Rajbari District, Bangladesh - Bapari, Md. Yahia (Traektorii͡a︡ nauki : mezhdunarodnyĭ ėlektronnyĭ nauchnyĭ zhurnal, 2016)
The study was analyzed the determinants, costs and benefits and resources allocation of both conventional and high yielding rice cultivation over the Rajbari district of Bangladesh. Data were accumulated from 300 regular rice growers of conventional and high yielding varieties and random sampling technique was applied for selecting the respondents from the study area from which information was collected through pre-tested questionnaire. Cobb – Douglas production function and gross margin were mainly used to determine the productivities and profits of both rice and the marginal value of the product was highly recommended to derive the optimal use of the resources. Results obtained by applying ordinary least square method showed that the most important factors of production in the study area were irrigation, labor, fertilizer and insecticide costs whose elasticities were 0.904, 0.048, 0.045 and 0.044 respectively and insignificant factors were seed and ploughing costs whose elasticities were – 0.009 and 0.030 respectively for high yielding rice. On the other hand, irrigation, insecticide, seed and ploughing costs of elasticities 0.880, 0.589, 0.116 and – 0.127 respectively were the important factors and minor role playing factors were labor and fertilizer costs whose elasticities were 0.098 and 0.077 respectively for conventional yielding rice. The core message from productivity analysis was that the irrigation was key variable which played a positive and vital role in producing rice of both varieties. All variables (resources) were economically misallocated in the production activities of both varieties along the study area but high yielding rice was more profitable than conventional one. Results also showed that the farmers of the study area produced rice of both varieties in the inefficient range of production. Continuous supply of electricity, flexible credit and improving the existing resources were the prime policy recommendations of producing more rice efficiently in future in the study area.